(untitled) (Olhar de Professor, 2020)
Inclusion in the educational environment is a continuous challenge in many educational institutions and is characterized by multiple actors, bias, conflicts and lack of clear information. Although the operational guidelines for Specialized Educational Assistance are required by law, the practical implementation of such guidelines depends on contextual immersion where it is applied. The purpose of this paper is to identify activities necessary for the inclusion of students with Specific Educational Needs through an approach involving Problem- Structuring Methods. For this purpose, a multi-methodology was assembled that combines the classical approaches of Value-Focused Thinking and Soft System Methodology. The constructed multi-methodology was applied in a case study in a unit of the Federal Education System. The main results indicate that some established assumptions should be re-evaluated in the light of the present study.